UPAYA CLEAN CLOTHES CAMPAIGN MEMBANTU TUNTUTAN PEKERJA PT JABA GARMINDO TERHADAP UNIQLO TAHUN 2015-2020 - Reis Henriques, Leticia Carla Dos; Dharmasih, D.W. Wiwik; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2021)
This research aims to analyze the endeavors made by (CCC) in helping pt Jaba Garmindo's labor demands against Uniqlo in 2015-2020. This.research.is.qualitative.descriptive.research using.the concept.of.human rights and transnational social movements. Data is obtained from various scientific journals, books, news, and articles related to the object being considered. The findings show that the efforts made by the Clean Clothes Campaign (CCC) are campaigning for changes in working conditions to be more humanist for workers in the fast fashion industry by voicing various human rights infringements that afflict workers on the international scene. In taking action Uniqlo will join many other global brands including H&M, Nike, Adidas, and Walmart that have legally taken over responsibility and provided workers with unpaid severance after bankruptcy and factory closures.   Keywords: Clean Clothes Campaign (CCC), U NIQLO , Human Rights